Nucleosome phasing and micrococcal nuclease cleavage of African green monkey component alpha DNA. - Musich, P R (1982)
The micrococcal nuclease cleavage of intact nuclear chromatin from African green monkey cells and of the completely deproteinized sequences was studied by using high-resolution analytical and DNA sequencing gels and secondary restriction enzyme analysis. When deproteinized component alpha DNA was used as substrate, not all phosphodiester bonds in the 172-base-pair repeat units were cleaved with equal frequency by the nuclease. A distinct preference for the cleavage of A-T rather than G-C bonds was observed; however, A + T-richness in itself did not confer susceptibility to cleavage by micrococcal nuclease. The results suggested that, in deproteinized DNA, nuclease cleavage at particular dinucleotides may be influenced more by the effect of adjacent sequences than by the composition of the dinucleotide. In contrast to complex cleavage patterns of the deproteinized component alpha DNA which arose because of multiple cleavage sites in the repeat unit, micrococcal nuclease cleaved component alpha nuclear chromatin at one site per nucleosome repeat, near position 126 in the nucleotide sequence. This simple chromatin cleavage pattern is consistent with the discrete nucleosomal structure of component alpha in chromatin and a direct phase relationship between the component alpha DNA sequence repeats and the nucleosome protein structural repeats.